Tamoxifen improves homeostasis in the peri-implant bone remodeling of osseointegrated titanium implants - Fiorin, Luiz Guilherme [UNESP]; Matheus, Henrique Rinaldi [UNESP]; Ervolino, Edilson [UNESP]; Canciani, Elena; Pellegrini, Gaia; Dellavia, Claudia; Maiorana, Carlo; de Almeida, Juliano Milanezi [UNESP] (Wiley, 2022)
Background: The purpose of this preclinical study was to evaluate the influence of tamoxifen (TAM) on the peri-implant bone remodeling of osseointegrated titanium implants in ovariectomized female rats. Materials and Methods: Seventy-two female rats underwent bilateral ovariectomy 20 weeks before implants placement. One titanium implant was inserted in each tibia of the animals. Six weeks following the implant surgery, animals were randomly divided into two experimental groups (n = 36), which received either saline solution (SS) or tamoxifen citrate (TAM) via gavage until euthanasia. Euthanasia was performed at 30, 60, and 90 days after the first gavage. Assessments of bone to implant contact (BIC), bone ingrowth percentage (BIN), morphological description of cellular and tissue reactions, immunohistochemistry for the detection of bone morphogenetic protein 2/4 (BMP2/4), runt-related transcription factor 2 (RUNX-2), osteocalcin (OCN) and tartrate-resistant acid phosphatase (TRAP), and bone chemical composition through scanning electron microscopy with energy-dispersive x-ray spectroscopy were performed. Results: Tamoxifen group presented higher BIC, higher BIN, higher RUNX-2 and OCN, lower TRAP-positive cells/mm2, and no differences regarding BMP-2/4 positive cells/mm2 than SS group in all periods. TAM group also showed higher Ca/P rate than SS group. Conclusion: Tamoxifen enhanced the remodeling of the bone surrounding titanium implants in ovariectomized rats.
Keywords: bone remodeling; dental implants; selective estrogen receptor modulators; tamoxifen